Trabalhadoras domésticas e suas filhas: um estudo sobre as percepções de mobilidade social em duas gerações - Leão, Leilyane Souza (Universidade Federal de São Carlos, 2023)
This work aims to understand the perceptions of social mobility of two generations from popular class families. The participants of the research were domestic workers who migrated between the late 1960s and the mid-1990s to the Southeast of the country and their daughters inserted in the context of the 2010s and 2020s. We tried to access mothers’ and daughters’ perceptions about their strategies to break with a particular social situation of origin. In the case of mothers, the hypothesis is that they found in domestic employment an alternative to break with a routine of hard and precarious work in the plantations. In the case of daughters, we tried to investigate how elongated schooling allowed the access to other professions different of their mothers' occupation. In this sense, we take into consideration the creation of public policies for education, especially the expansion of access to higher education between the decade of 2000 and 2010. Considering the transformations in domestic work between two generations from working class families, the objective of this study is to understand the relationships among migration, generation, gender, and social mobility in contemporary Brazil. Through the method of life stories, trajectories, and narratives, we sought to access the perceptions and meanings attributed by the participants of this research to their mobility experiences.
Domestic workers and their daughters: a study on perceptions of social mobility in two generations
Las trabajadoras domésticas y sus hijas: un estudio sobre la percepción de la movilidad social en dos generaciones
Keywords: Trabalho doméstico; Migração; Gênero; Geração; Mobilidade social; Domestic workers; Migration; Gender; Generation; Social mobility; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA